Model Pengajaran Bahasa dengan Pendidikan yang Memanusiakan - Manurung, Rosida Tiurma (Zenit, 2012)
Modern, digitalized, high tech, global era characterized by the development of sciences has transformed human beings into  heartless machines with no sense of humanity and no concerns  of  their environment. Therefore, education should be packed with the perspective of humanism. Education should not be interpreted as a mere class teaching-learning activity; however, it should refer to the various processes and activities that  should be productive; creative; include skills development, personality, integration, and excellence; as well as moral and spiritual reinforcement. Education should be managed and directed with clear objectives in order to develop positive values in learners. Education should be able to create figures with solid and proven character and personality both in the field of science and humanity. Humanizing education is the capablity of producing humans with sense of "humanity", characterized by helpfullness; empathy; honesty; sharing with others; loyalty;  the willingness to take valuable lessons; being persistent and tenacious,; having high-respect of pluralism; tolerance; respect to others; patience; replied good for evil; always putting the good rather than evil, having continuous efforts to improve the quality of charity and kindness; humility; and sincerity. Therefore, the teaching materials must also be interpreted, filled, and imbued with the messages of humanity. These  entire  facts  mean  that  teaching materials are not mere “soulless and empty” materials since if it is, then the materials will be like an empty casket with no benefits to humanity. An approach of  humanism in modern era education is considered the most  appropriate solution since it does not work like a machines. This means the students, teachers, and teaching materials should also be “humanized” in order to achieve educational goals  optimally and in accordance with the vision and mission of education. This research discusses model of language teaching with humanistic perspective. Through language teaching with humanism approach, it is expected that, students and teachers may rediscover the "human side" that might have been lost and undetected.  Keywords: models of language teaching, humanism, teachers, students, the modern era.